Thickness of endometrium: predictor of the effectiveness of IVF/ICSI programs (literature review) - L A Bagdasaryan; I E Korneyeva (IP Berlin A.V., 2018)
The aim of the study is to systematically analyze the data available in the modern literature on the relationship between endometrial thickness and the frequency of pregnancy in the program of assisted reproductive technologies (ART). Materials and methods. The review includes data from foreign and domestic articles found in PubMed on this topic. Results. The article presents data on the relationship between the thickness of the endometrium and the frequency of pregnancy in ART programs. The greatest number of studies is devoted to the evaluation of the relationship between the thickness of the endometrium and the frequency of pregnancy on the day of the ovulation trigger. Data are presented on the existence of a correlation between the thickness of the endometrium measured on the day of the ovulation trigger and the frequency of clinical pregnancy, as well as data on the need to evaluate the structure of the endometrium and the state of subendometric blood flow. The importance of multilayered (three-layered) endometrium as a prognostic marker of success in in vitro fertilization/intracytoplasmic sperm injection programs in the ovum is emphasized. The conclusion. The thickness of the endometrium can not be used as an argument for canceling the cycle or abolishing embryo transfer to the uterine cavity. Further studies in this direction are needed with a study of the morphological and molecular genetic characteristics of the endometrium, which in the future will allow us to evaluate the relationship between the thickness of the endometrium and the probability of pregnancy.